2020
DOI: 10.1038/s41379-020-0639-4
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 can infect the placenta and is not associated with specific placental histopathology: a series of 19 placentas from COVID-19-positive mothers

Abstract: Congenital infection of SARS-CoV-2 appears to be exceptionally rare despite many cases of COVID-19 during pregnancy. Robust proof of placental infection requires demonstration of viral localization within placental tissue. Only two of the few cases of possible vertical transmission have demonstrated placental infection. None have shown placental expression of the ACE2 or TMPRSS2 protein, both required for viral infection. We examined 19 COVID-19 exposed placentas for histopathologic findings, and for expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
292
2
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 249 publications
(341 citation statements)
references
References 36 publications
27
292
2
20
Order By: Relevance
“…Importantly, there was also cytotrophoblast and extravillous trophoblast expression of ACE2. In contrast, no ACE2 expression was detected in villous stroma, Hofbauer cells, or endothelial cells [14]. ACE2 protein is enriched per unit volume in the placenta and ovary, compared to other tissues, despite a low mRNA level detected in the two tissues [15].…”
Section: Key Issues Related To Pregnancy Associated With Covid-19mentioning
confidence: 82%
See 2 more Smart Citations
“…Importantly, there was also cytotrophoblast and extravillous trophoblast expression of ACE2. In contrast, no ACE2 expression was detected in villous stroma, Hofbauer cells, or endothelial cells [14]. ACE2 protein is enriched per unit volume in the placenta and ovary, compared to other tissues, despite a low mRNA level detected in the two tissues [15].…”
Section: Key Issues Related To Pregnancy Associated With Covid-19mentioning
confidence: 82%
“…Smithgall and colleagues found no evidence of direct viral infection of the placenta, using in-situ hybridization (ISH) for the S-gene encoding the spike protein and immunohistochemistry with the monoclonal-SARS-CoV-2 spike-antibody 1A9 [12]. Conversely, in two of 19 cases reported by Hecht et al [14], SARS-CoV-2 RNA was present in placental villi focally, in both the ST and cytotrophoblast [14]. Moreover, three of 11 placentas having swabs taken from villi and fetal membranes tested positive for SARS-CoV-2 [16].…”
Section: Key Issues Related To Pregnancy Associated With Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Individual and combinations of abnormalities of maternal vascular malperfusion, fetal vascular malperfusion, inflammatory lesions including chorioamnionitis and villitis, and even absence of pathology findings have been reported in placentas from neonates testing negative for COVID-19. The significant variance in pathology findings among non-transmitting placentas has led to one article entitled "SARS-CoV-2 can infect the placenta and is not associated with specific placental histopathology" [40].…”
Section: Discussionmentioning
confidence: 99%
“…In 2 hospitals in Boston, Hecht et al examined placentas from 19 pregnant women having COVID-19 in the peripartum period and compared the findings with 3 sets of control placentas from women who were uninfected with the coronavirus [40]. The authors found that there were no specific gross or microscopic findings in placentas from women with COVID-19.…”
Section: Placental Pathology From Mothers With Covid-19 In the Absencmentioning
confidence: 99%